Flow topology around low reynolds number airfoils with vortex shedding - Che Ibrahim, Che Intan Hartini; Abdullah, Aslam (Penerbit Akademia Baru, 2020)
In depth studies on the vortex formation process as well as the periodic behavior of the reattachment profile have been mainly sparked by broad discussions on the flow topology. While the topology methodology is quite well established, the majority of airfoil types have still not been covered. In this study, six low Reynolds number airfoils were considered to investigate the separation bubble structure, vortex shedding and reattachment point. This was done by means of computational fluid dynamics simulations involving the airflow passing several Eppler and Selig models. The method was validated against an established mathematical relationship to indicate that both simulations and analysis technique were reliable. It was observed that the phenomena under investigation directly affect the airfoils aerodynamic performance. In particular, vortex shedding and big reattachment length contribute to the minimum lift. Moreover, high number of vortices in the separation bubble as well as secondary separation bubble result in maximum drag. The results which correspond to low Reynolds number airfoils are applicable in micro aerial vehicles field.